The Oral History Program: III. Personal views of health sciences librarianship and the Medical Library Association. - McKenzie, D (1998)
The Medical Library Association Oral History Program uses accepted oral history techniques to collect and preserve interviews with members. The original taped interviews and transcripts are kept in the Medical Library Association archives and made available for research purposes; edited copies of the interviews are distributed through the National Network of Libraries of Medicine, and members are encouraged to borrow and read the histories. Summaries of forty-three interviews provide personal views on health sciences librarianship and the Medical Library Association.